2018
DOI: 10.24203/ajas.v6i6.5651
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rainfall and Temperature Trends in Bahati Sub-County, Kenya

Abstract: This study analyzed the climate variability trends in Bahati Sub-County, Kenya for the period 1985 to 2015.The climate parameters used included rainfall onset, rainfall cessations, seasonal rain, annual rainfall, annual mean temperature, maximum and minimum temperature. Data on rainfall and temperature was collected from Nakuru Meteorological Station. The strength and direction of the relationship between rainfall and temperature was determined using SPSS software version 23 (correlation analysis) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…The findings of this study concur with those of Kimani [25], who predicted that higher temperature variability throughout the OND season would result in a decrease in kidney bean seed production. The results of the regression model also support the findings of Koimbori [30], who reported that maize yield decreased as temperature rose. The observed findings may imply that there has been increasing temperatures in the area that may be associated with decline in green gram yield.…”
Section: Regression Analysis For Temperature and Green Gram Yieldsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings of this study concur with those of Kimani [25], who predicted that higher temperature variability throughout the OND season would result in a decrease in kidney bean seed production. The results of the regression model also support the findings of Koimbori [30], who reported that maize yield decreased as temperature rose. The observed findings may imply that there has been increasing temperatures in the area that may be associated with decline in green gram yield.…”
Section: Regression Analysis For Temperature and Green Gram Yieldsupporting
confidence: 86%
“…Mkonda [29] also found a strong relationship amongst rainfall and crop output. Similarly, Koimbori [30] reported a high correlation between rainfall patterns and maize production that is significant, favorable, and supportive. It is possible that the increased adaption to climate change through use of certified seeds, maximum soil cover, minimum tillage, crop rotation and weather advisories may have resulted in an increase in output from 2019 to 2021.…”
Section: Trends Of Green Gram Yield From 2002 To 2021mentioning
confidence: 84%